The role of autophagic kinases in regulation of axonal function - Berth, Sarah H.; Rich, Dominick J.; Lloyd, Thomas E. (Frontiers in Cellular Neuroscience, 2022)
Autophagy is an essential process for maintaining cellular homeostasis. Highlighting the importance of proper functioning of autophagy in neurons, disruption of autophagy is a common finding in neurodegenerative diseases. In recent years, evidence has emerged for the role of autophagy in regulating critical axonal functions. In this review, we discuss kinase regulation of autophagy in neurons, and provide an overview of how autophagic kinases regulate axonal processes, including axonal transport and axonal degeneration and regeneration. We also examine mechanisms for disruption of this process leading to neurodegeneration, focusing on Amyotrophic Lateral Sclerosis.